2015
DOI: 10.1007/s10967-015-4285-0
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive study on iodine uptake by selected LDH phases via coprecipitation, anionic exchange and reconstruction

Abstract: We explored the use of selected layered double hydroxides (LDHs) of different compositions and obtained by means of different routes (i.e., coprecipitation, anionic exchange and reconstruction) as iodine/iodate adsorbents. The influence of speciation (iodide vs. iodate) on iodine uptake was rather strong, resulting in much lower iodide incorporation. The Fourier transform of iodine K X-ray absorption edge data (EXAFS) of all iodate-LDHs showed a single I-O scattering path of 1.8 Å . Thermal stability and leach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Layered double hydroxides (LDHs) possess positively charged layers and exchangeable interlayer anions. Due to the particular compositions and structures, LDHs acting as sorbents have displayed a vast perspective in removing environmental contaminants . Ma et al reported [S x ] 2– -intercalated LDH (MgAl-S x -LDH) and found that interlayered [S x ] 2– reduced I 2 to [I 3 ] − ions which were immobilized within the LDH gallery, realizing a maximum iodine capture ( q m ) of 1520 mg/g .…”
Section: Introductionmentioning
confidence: 99%
“…Layered double hydroxides (LDHs) possess positively charged layers and exchangeable interlayer anions. Due to the particular compositions and structures, LDHs acting as sorbents have displayed a vast perspective in removing environmental contaminants . Ma et al reported [S x ] 2– -intercalated LDH (MgAl-S x -LDH) and found that interlayered [S x ] 2– reduced I 2 to [I 3 ] − ions which were immobilized within the LDH gallery, realizing a maximum iodine capture ( q m ) of 1520 mg/g .…”
Section: Introductionmentioning
confidence: 99%
“…In aqueous environments and soil systems, iodine exists mainly as iodide (I À ) and iodate (IO 3 À ). 7,8 In some cases, IO 3 À is the predominant iodine form, which accounts for up to approximately 70% of total iodine, with iodide and organoiodine being minor components. 9,10 The fate and mobility of iodine in soils depend largely on its interactions with soil components.…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35][36][37][38][39] The underlying mechanisms of sorption of anions by LDHs includes: 7,33 (1) anion exchange; (2) surface adsorption; and (3) reformation. Although LDH shows a relatively high potential sorption capacity for iodine anions, the presence of competing anions, including carbonate, phosphate and sulphate, has a signicant impact on uptake of the target anions from an aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation